The Relevant Role of Navigated Tractography in Speech Eloquent Area Glioma Surgery: Single Center Experience - Luca Francesco Salvati (MDPI AG, 2021)
Background: Gliomas are among the most challenging pathologies for neurosurgeons due to their infiltrative and recurrent nature in functionally relevant regions. Current knowledge confirms that gross total resection highly influence survival in patient with glioma. However, surgery performed in eloquent brain area, could seriously compromise the quality of life in patient with reduced life expectancy even more if it concerns the language function. Methods: 18 right-handed patients with perisylvian gliomas on the left hemisphere were prospectively analyzed over a period of 12 months. Standardized preoperative Diffusion-Tensor-Imaging based tractography of the five main language Tracts (Arcuate Fasciculus, Frontal Aslant Tract, Inferior Fronto-Occipital Fasciculus, Inferior Longitudinal Fasciculus, Uncinate Fasciculus) was navigated during the surgical procedure. Using a validated method, correlations were made between the pre-operative fascicles and their possible infiltration and surgical damage. The language status was assessed using the Aachen Aphasia Test. Results: In all nine patients who developed a permanent disorder there was pre-operative involvement of at least one fascicle and resection of at least one of these. In this way, areas of high risk of permanent language damage have emerged as a result of surgical injury: the temporoparietal junction, the middle portion of the FAT and the temporal stem. Conclusions: Navigated tractography has proven to be a user-friendly tool that can assess perioperative risk, guide surgical resection, and help the neurosurgeon to find that balance between tumor resection and function preservation.